The cult of the body and old age. Psychological reflections - Lidia Anna Wiśniewska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2015)
In modern society body plays significant role, thus becoming a great value. As young and healthy body is promoted, the majority of research explorations focuses on young people. However, due to ageing societies, more and more researchers investigate the problem of experiencing one's body by middle-aged and elderly people. The main aim of this paper is to analyse the research on body in a group of elderly people. Also, the article attempts to answer the question as to what extent the cult of body can refer to this group. The results of research are often contradictory and it is difficult to clearly indicate how satisfaction with body changes across the life span and to what extent health and fitness become more important than looking attractive in elderly people.